Management of Pregnancy in Women with Antithrombin III Congenital Defect: Report of Four Cases - De Stefano, V; Leone, G; De Carolis, S; Ferrelli, R; Di Donfrancesco, A; Moneta, E; Bizzi, B (Thrombosis and Haemostasis, 1988)
Four pregnant women with antithrombin III congenital deficiency underwent thrombosis prophylaxis including oral antico–agulants administered from the 16–18th week to the 36–37th week of pregnancy, subcutaneous heparin before the 16–18th week and after the 36–37th week, and a single infusion of AT III concentrate in the peripartum period in order to obtain a minimal level of 0.8 U/ml of AT III functional activity. The level of circulating AT III after the concentrate infusion needs to be evaluated by functional methods, because of a consistent amount in the concentrates of inactive AT III immunoreactive material. No thrombotic or haemorrhagic complication occurred after starting prophylaxis in any woman either in any newborn.
Keywords: AT III congenital deficiency; Pregnancy; Thrombosis prophylaxis; Heparin; Oral anticoagulants; AT III concentrate